The city of London and British social democracy, c. 1959 – 1979 - Davies, A (2014)
This thesis considers the position of the British financial sector in the economic strategy of social democracy during the 1960s and 1970s. In doing so it attempts to shed light on a broader question – what caused the collapse of the postwar social democratic project in Britain during the final quarter of the twentieth century? It contends that the social democratic project faced a variety of challenges to its principles, assumptions, and practices in the two decades prior to the election of Margaret Thatcher as a result of changes to the financial system. These challenges offered opportunities for the advance of social democracy beyond the norms established following the Second World War, but the capacity to pursue these was constrained in a number of ways. The emergence of institutional investment, and the breakdown of the postwar banking settlement, undermined the social democratic methods for managing and controlling credit and investment, yet also offered the opportunity to advance the State’s capacity to intervene in the economy. However the ability of the left to renew and rebuild the social democratic economic project along more advanced, interventionist lines was limited by new material constraints which made extensive reform of the financial system and the domestic economy extremely difficult. Structural changes to the international financial system following the breakdown of the Bretton Woods settlement, combined with the severe economic crisis of the 1970s, imposed new limits on the freedom of governments to engage in domestic-focused macroeconomic management. As the methods and techniques of social democratic economic strategy became less effective, the ideal of developing an advanced industrial economy through State coordination faded. In its place a new conception of the British economy was promoted which sought to revive its historic liberal and internationalist role in which the City of London was at its heart.